PEMIKIRAN POLITIK IMAM KHOMEINI: KONSEP WILAYAH AL-FAQIH DAN PENERAPANNYA DI ZAMAN SEKARANG - Rofiki Rofiki (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2022)
Abstract: Imam Khomeini's political thought has made a very large contribution, especially to his own country, Iran. The concept of the Wilayah al-Faqih that he developed later became the most important element of the government system of the Islamic Republic used by Iran after the collapse of the monarchical regime of Shah Reza Pahlavi. The Wilayah al-Faqih is a government concept that gives an important position to the fuqaha (ulama). However, even though on the one hand this concept is ideal, on the other hand it has led to the dominance of the ulama leadership. The people, as an important component and the main control in (pure) democracy, have a very low role. This is what then in the following phases, the concept of Wilayah al-Faqih received criticism from some circles. Keywords: political thought; Wilayah al-Faqih; ulama; Imam Khomeini.